Inquiry-Based Learning and Its Role in Students’ Writing Achievement: Pembelajaran Berbasis Penelitian dan Perannya dalam Pencapaian Menulis Siswa - Putri, Cornelia Ayu Wanda; Novita, Dian (Indonesian Journal of Education Methods Development, 2024)
This study investigates the role of Inquiry-Based Learning (IBL) in improving students' writing achievement, particularly in descriptive texts. Background: Writing is a critical skill that many students struggle to master, especially in vocational settings. Specific Background: Observations indicated that students at SMK Muhammadiyah 1 Taman faced challenges in completing writing assignments, primarily due to difficulties with components such as vocabulary, grammar, and structure. Knowledge Gap: Although various teaching methods exist, limited research has focused on the impact of IBL on writing skills in this context. Aims: This research aims to evaluate whether IBL can enhance students' descriptive writing capabilities. Results: Utilizing a pre-experimental design with pre-test and post-test assessments on a sample of 25 students, results revealed a significant improvement in writing achievement, as evidenced by a t-test value of 22.472, exceeding the critical value of 2.036. Novelty: This study contributes to the literature by demonstrating the effectiveness of IBL as a pedagogical approach in vocational education settings. Implications: The findings suggest that implementing IBL can foster students' writing skills, encouraging greater engagement and proficiency in descriptive text composition. Highlights: Inquiry-Based Learning: Students actively engage in the learning process, fostering critical thinking and creativity. Writing Achievement: Significant improvement observed in students' descriptive writing skills after applying IBL methods. Pre-Experimental Design: The study utilized a pre-test and post-test approach to assess writing performance effectively. Keywords: Inquiry-Based Learning, descriptive writing, student engagement, writing skills, educational research.